Populasi Lalat Buah Disampling Menggunakan Metil Eugenol pada Tanaman Cabai di Kabupaten Ogan Ilir, Sumatera Selatan - Aksel Santoso; Alfian Bustommi; Irenius Tegar Setiawan; Rafael Ika Rahayu; Reza Demaila Miranda; Riki Suranta Sembiring; Abu Umayah; Bambang Gunawan; Ars Arsi (xxxx-xxxx, 2023)
Santoso A, Bustommi A, Setiawan IT, Rahayu RI, Miranda RD, Sembiring RS, Umayah A, Gunawan B, Arsi A. 2022. Population of fruit flies besides using methyl eugenol on chili plants in Ogan Ilir Regency, South Sumatra. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-10 Tahun 2022, Palembang 27 Oktober 2022. pp. 120-128. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).The attack of fruit flies (Bactrocera spp.) on red chili plants is one of the important problems in the red chili production process. In general, farmers still choose to use synthetic pesticides in controlling fruit flies. However, this control method has a negative impact, namely it can cause resistance and resurgence of the target pest. This review aimed to provide information about the benefits of compounds through bioattractants combined through the application of attractant traps in controlling fruit flies. This writing method uses a literature study which is analyzed and developed into an easy-to-understand review. Extraction contains methyl eugenol reaching 70-96%. The liquid compound methyl eugenol can be an attraction for male fruit flies. The trap attractant system has the ability to stimulate the interest of fruit flies and can be used for a long time. The application of trap attractants causes sexual communication disorders so that mating disorders occur in fruit flies. The conclusion obtained from the writing of this scientific paper is that the methyl eugenol compound in chili plants can be used as a control system.